Nutrition Education Intervention on Feeding Practice for Children with Wasting: Systematic Literature Review - Prabawangi, Ega Galuh; Lestari, Anik; Suminah, Suminah (Proceeding of International Conference on Special Education in South East Asia Region, 2023)
Wasting is one of the nutritional problems in Indonesia with a prevalence of 7.1% (2021). This prevalence is still above the standard set by WHO (5%). Children under 5 years old with wasting nutritional status will experience stunted growth and development that can affect their productivity in the future. Nutrition education on feeding practice given for mothers aims to improve mothers’ knowledge and skill in the practice of feeding and drinking according to WHO recommendation and to overcome wasting. Method used in this research was Systematic Literature Review (SLR) on journals published from 2019 to 2023. These journals were collected from Google Scholar Database. This research had several research questions. The results showed that when mothers’ knowledge and skill in the practice of feeding and drinking improved.